2015
DOI: 10.1007/s00056-015-0293-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of temporomandibular disorder pain with awake and sleep bruxism in adults

Abstract: When occurring separately, awake and sleep bruxism are significant risk factors for TMD pain. In case of simultaneous presence, the risk for TMD pain is even higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 25 publications
2
40
1
7
Order By: Relevance
“…A recent systematic review on the epidemiology of bruxism in adults retrieved only a couple of papers on AB, reporting a 22.1% prevalence, as defined by the frequency term “often”, and a 31% prevalence, independent on the frequency, during the past 6 months . A successive paper reported a 11.2% prevalence based on the generic history‐taking item “During the day, do you grind your teeth or clench your jaw?”, while an investigation on Brazilian dental students found a 36.5% prevalence, as identified by the question “In the last 30 days have you noticed clenching your teeth while awake and not chewing food?” …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review on the epidemiology of bruxism in adults retrieved only a couple of papers on AB, reporting a 22.1% prevalence, as defined by the frequency term “often”, and a 31% prevalence, independent on the frequency, during the past 6 months . A successive paper reported a 11.2% prevalence based on the generic history‐taking item “During the day, do you grind your teeth or clench your jaw?”, while an investigation on Brazilian dental students found a 36.5% prevalence, as identified by the question “In the last 30 days have you noticed clenching your teeth while awake and not chewing food?” …”
Section: Discussionmentioning
confidence: 99%
“…23 A successive paper reported a 11.2% prevalence based on the generic history-taking item "During the day, do you grind your teeth or clench your jaw? ", 24 while an investigation on Brazilian dental students found a 36.5% prevalence, as identified by the question "In the last 30 days have you noticed clenching your teeth while awake and not chewing food?". 25 As for the specific AB activities, the few literature data suggest that non-functional tooth contacts (ie, teeth contacts during activities not associated with normal functions, such as reading books, watching television, working etc…), recorded at 20-minute intervals for 10 days, were reported by 9.6% of TMD-free subjects recruited as controls in a recent paper assessing the possible role of teeth contacting habits as a risk factor for TMD.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that the close functional coupling of these muscle groups may be involved in the aetiology of myofascial pain conditions . In particular, it is believed that biomechanical interactions resulting from bruxism are risk factors in the multifactorial aetiology of myofascial jaw and neck pain …”
Section: Introductionmentioning
confidence: 99%
“…14 In particular, it is believed that biomechanical interactions resulting from bruxism are risk factors in the multifactorial aetiology of myofascial jaw and neck pain. [15][16][17][18][19] Electromyographic (EMG) monitoring of the co-contraction behaviour of masticatory and neck muscles has been conducted under conditions of pathophysiologic loading of the masticatory muscles, for example jaw clenching or tooth grinding. [20][21][22][23] In this context, most studies on the neck musculature have been performed by use of surface electrodes and under maximum contraction of the jaw muscles.…”
mentioning
confidence: 99%
“…Recently, it was shown that self-reported awake bruxism was associated with TMD pain complaints [14,15]. This observation can be supported by the results of experimental studies, which demonstrated that clenching can aggravate masseter muscle pain in patients with TMD [16].…”
mentioning
confidence: 76%